Engineering future decisions joint ICE/ACSE [i.e. ASCE]/CSCE conference. (Thomas Telford, 1987)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a joint ASCE/ICE/CSCE conference held in London and Edinburgh in 1987.